PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA CREW CUTS STUDIO BARBERSHOP MAUMERE - Ferdinandus Constante Poling; Antonius Philipus K.Gheta; Nunsio Handrian Meylano (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to describe Customer Loyalty, Service Quality, and Customer Satisfaction and to analyze the influence of Service Quality and Customer Satisfaction on Customer Loyalty, both partially and simultaneously. The population in this study were customers who received services at Crew Cuts Studio Barbershop Maumere. The sample size used in this study was 96 people using the Cochran formula. The descriptive analysis results indicate that the Customer Loyalty variable falls within the good criteria, the Service Quality variable falls within the good criteria, and the Customer Satisfaction variable falls within the good criteria. The t-test statistics indicate that partially, the service quality variable does not significantly influence customer loyalty. Furthermore, partially, the customer satisfaction variable does not significantly influence customer loyalty. The f-test statistics indicate that both service quality and customer satisfaction have a significant effect on customer loyalty. The results of the determination analysis indicate that both independent variables in this study are able to explain the relationship between the independent variables and customer loyalty, which is interpreted as low.